REAKTUALISASI NILAI-NILAI PANCASILA DI MADRASAH ALIYAH NAHDLATUL ULAMA DEMAK DALAM PERSIAPAN PEMILU 2024 - Suwandi, Dedy; Junaidi, Muhammad; Yulistyowati, Efi; Dewi Rosaria, Stefani (Fakultas Hukum Universitas Semarang, 2023)
The values of Pancasila as a guideline for Indonesian citizens to make Pancasila a guiding spirit in running the governance of personal and social life of the nation and state. Pancasila as a spirit to carry out the value of national values is truly an inclusive social virtue, inspiring, uniting and liberating all social groups, ethnicities, religions, languages and aspirations of national life in the midst of society. The values of Pancasila are currently discussed regarding the virtues in the preparation of elections for novice voters. Pancasila every time the ceremony is often mentioned together but the values in Pancasila most do not know in full so that the values in Pancasila need to be re-applied so that it enters into the inner spirit of the students at MA NU Demak. Exploring the values of Pancasila as a guideline in the election can certainly serve to integrate diversity (diversity) despite different choices but still unite. The values of Pancasila are needed to anticipate and face a series of problems in the election including the spread of fake news, black campaigns, and money politics. This can be anticipated when the soul in every human being is instilled with the seeds of love for the country. The spirit of nationality reminds us of the importance of commitment, loyalty of every child of the nation to remain consistent in the fundamental orientation of national life, the love of one homeland, one language and one nation Indonesia.